Assessing the Impact of Tuberculosis on Economic Growth in ASEAN Countries: A Conceptual Framework and Panel Data Analysis - Fitriangga, Agus; Alex, Alex (Jurnal Ekonomi Kesehatan Indonesia, 2024)
Tuberculosis (TB) remains a major global health issue, particularly in Southeast Asia, where its impact extends beyond public health to affect economic performance. This study evaluates the economic implications of TB incidence on gross domestic product (GDP) growth across eight ASEAN countries from 2000 to 2020. We employed a panel data regression approach, utilizing Common Effect Model (CEM), Fixed Effects Model (FEM), and Random Effects Model (REM) to analyze the relationship between TB incidence and economic growth. The dataset included annual GDP figures, TB incidence rates, foreign direct investment (FDI), labor force size, and trade openness, sourced from international databases. The most appropriate model was selected based on Chow and Hausman tests, with FEM being the preferred model for its ability to account for country-specific effects. The FEM analysis revealed a significant negative impact of TB incidence on GDP, with a reduction of approximately 6.69% in GDP growth for each unit increase in TB incidence. Simulations showed that countries with high TB prevalence, such as the Philippines and Cambodia, experienced substantial economic losses, while reductions in TB incidence could lead to notable economic gains, particularly in Indonesia and Thailand. The study highlights the considerable economic burden of TB on ASEAN countries and emphasizes the importance of integrating TB control measures into economic development strategies. Effective TB prevention and treatment could substantially mitigate economic losses and promote sustainable growth. Policymakers are encouraged to invest in TB healthcare infrastructure and consider the economic benefits of reducing TB incidence in their health policies.